ISLAM AND THE CONCEPT OF TOLERANCE AND CO-EXISTENCE - Sho'ala, Abdulnabi AI (1994)
The human conscience seems to have come to a stage to put a stop to the exploitation of religions in the pursuit of political gains or the settlement of long-standing disputes. This trend has been clearly manifested in the recent discussions to find a peaceful solution to some of the bloodiest and most violent conflicts in recent times attributed to religious or ethnic differences such as the Arab-Israeli conflict, crisis in Ireland or the ethnic problem in Bosnia.
Keywords: CO-EXISTENCE; Islam; Tolerance